Pengaruh Penerapan Model Pembelajaran Aktif Tipe Learning Start With A Question Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran Ekonomi Di Kelas X SMAN 8 Kota Jambi - Putri, Septiani Eka; Elfonda, Elfonda; Oktavia, Dina Dwi (SJEE (Scientific Journals of Economic Education), 2024)
This research aims to determine the effect of implementing the Learning Start with a Question type active learning model on students' learning motivation in Economics subjects in class X SMAN 8 Jambi City. This type of research uses quantitative research methods with a descriptive analysis approach and simple linear regression analysis techniques. The results of the research show that the active learning model of the Learning Start with a Question type has a significant effect on students' learning motivation in class X Economics at SMAN 8 Jambi City.